Identitas Perempuan Multikultural dalam Cala Ibi Karya Nukila Amal - Maharani Intan Andalas (Jurnal Lingua Idea, 2017)
This research aims to describe a multicultural woman identity in Cala Ibi novel written by Nukila Amal. The method uses qualitative method based on theory of pschoanalysis feminism. Through women character analysis, it found that women identity constructed in symbolic and imaginary phase. The women character resistance to symbolic order with creates other self. In imaginary phase, the other self is a woman with split identity who needs to be free and submissive at once. It voices multiculturalism point of view. The women approval to differences and cultural diversity shows her position as a multicultural subject. However, the women voice can also become desire for ‘other’ as result on alienation that faced by her in postmodern situation.